Yiqi Jiedu Huayu Decoction Alleviates Renal Injury in Rats With Diabetic Nephropathy by Promoting Autophagy - Xuan, Chen; Xi, Yu-Meng; Zhang, Yu-Di; Tao, Chun-He; Zhang, Lan-Yue; Cao, Wen-Fu (Frontiers in Pharmacology, 2021)
Diabetic nephropathy (DN), a common microvascular complication of diabetes, is one of the main causes of end-stage renal failure (ESRD) and imposes a heavy medical burden on the world. Yiqi Jiedu Huayu decoction (YJHD) is a traditional Chinese medicine formula, which has been widely used in the treatment of DN and has achieved stable and reliable therapeutic effects. However, the mechanism of YJHD in the treatment of DN remains unclear. This study aimed to investigate the mechanism of YJHD in the treatment of DN. Sprague-Dawley rats were randomly divided into a control group, a model group, an irbesartan group, and three groups receiving different doses of YJHD. DN animal models were constructed using streptozotocin and then treated with YJHD for 12 consecutive weeks. Blood and urine samples were collected during this period, and metabolic and renal function was assessed. Pathological kidney injury was evaluated according to the kidney appearance, hematoxylin-eosin staining, Masson staining, periodic-acid Schiff staining, periodic-acid Schiff methenamine staining, and transmission electron microscopy. The expression levels of proteins and genes were detected by immunohistochemistry, western blotting, and real-time qPCR. Our results indicate that YJHD can effectively improve renal function and alleviate renal pathological injury, including mesangial matrix hyperplasia, basement membrane thickening, and fibrosis. In addition, YJHD exhibited podocyte protection by alleviating podocyte depletion and morphological damage, which may be key in improving renal function and reducing renal fibrosis. Further study revealed that YJHD upregulated the expression of the autophagy-related proteins LC3Ⅱ and Beclin-1 while downregulating p62 expression, suggesting that YJHD can promote autophagy. In addition, we evaluated the activity of the mTOR pathway, the major signaling pathway regulating the level of autophagy, and the upstream PI3K/Akt and AMPK pathways. YJHD activated the AMPK pathway while inhibiting the PI3K/Akt and mTOR pathways, which may be crucial to its promotion of autophagy. In conclusion, our study shows that YJHD further inhibits the mTOR pathway and promotes autophagy by regulating the activity of the PI3K/Akt and AMPK pathways, thereby improving podocyte injury, protecting renal function, and reducing renal fibrosis. This study provides support for the application of and further research into YJHD.